From Toussaint to Tupac : the Black international since the age of revolution - West, Michael O. (Michael Oliver); Martin, William G., 1952-; Wilkins, Fanon Che (University of North Carolina Press, 2009)
"This collection of essays explores black internationalism--the struggle against oppression, whether manifested in slavery, colonialism, or racism. Contributors focus on three moments in global black history: the American and Haitian revolutions, the Garvey movement and the Communist International following World War I, and the Black Power movement of the late twentieth century to demonstrate how black internationalism emerged and influenced events in particular localities, how participants in the various struggles communicated across natural and man-made boundaries, and how the black international aided resistance on the local level, creating a collective consciousness"--Provided by publisher